Phase 1 trial, pharmacokinetics, and pharmacodynamics of dasatinib combined with crizotinib in children with recurrent or progressive high‐grade and diffuse intrinsic pontine glioma. Issue 7 (7th March 2018) - Broniscer, Alberto; Jia, Sujuan; Mandrell, Belinda; Hamideh, Dima; Huang, Jie; Onar‐Thomas, Arzu; Gajjar, Amar; Raimondi, Susana C.; Tatevossian, Ruth G.; Stewart, Clinton F.
Abstract: Background: Progressive/recurrent high‐grade and diffuse intrinsic pontine gliomas (DIPGs) are fatal. Treatments targeting molecular pathways critical for these cancers are needed. Methods: We conducted a phase 1 study (rolling‐six design) to establish the safety and maximum tolerated dose (MTD) of dasatinib, an oral platelet‐derived growth factor receptor A (PDGFRA) inhibitor, and crizotinib, an oral c‐Met inhibitor, in such patients. Pharmacokinetics of both agents were performed. Biomarkers of cellular pathway activation in peripheral‐blood mononuclear cells (PBMC) were evaluated before and after administration of dasatinib. PDGFRA and MET amplification, and PDGFRA mutations were studied in tumor samples. Results: Twenty‐five patients were enrolled in this study (median age: 11.9 years). Eleven patients had DIPG. Glioblastoma accounted for 40% of cases. Dasatinib at 50 mg/m 2 and crizotinib at 130 mg/m 2 or 100 mg/m 2 were poorly tolerated when administered twice daily. Drug administration was then switched to once daily. Dasatinib administered at 50 mg/m 2 and crizotinib at 215 mg/m 2 once daily was the MTD. Dose‐limiting toxicities consisted of diarrhea, fatigue, proteinuria, hyponatremia, rash, and grade 4 neutropenia. Only two patients received therapy for at least 6 months. No objective radiologic responses were observed. Pharmacokinetics of dasatinib and crizotinib were comparable to previous studies. A statistically significant decrease in the ratio of p‐AKT/total AKT in PBMC occurred after dasatinib administration. PDGFRA and MET amplification were found in four and two cases, respectively. Only one of 10 tumors harbored a PDGFRA mutation. Conclusions: This drug combination was poorly tolerated and its activity was minimal. We do not recommend further testing of this combination in children.